2022
DOI: 10.1152/ajpcell.00285.2021
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma concentration of kynurenine following intake of branched-chain amino acids are not caused by alterations in muscle kynurenine metabolism

Abstract: Administration of branched-chain amino acids (BCAA) has been suggested to enhance mitochondrial biogenesis, including levels of PGC-1α, which may, in turn, alter kynurenine metabolism. Ten healthy subjects performed 60 min of dynamic one-leg exercise at ~70% of Wmax on two occasions. They were in random order supplied either a mixture of BCAA or flavored water (placebo) during the experiment. Blood samples were collected during exercise and recovery, and muscle biopsies were taken from both legs before, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The contribution of kynurenine pathway metabolites can occur from several organ systems, with kynurenine mainly derived from the liver, whereas the conversion of kynurenine to kynurenic acid with exercise training is proposed to occur in muscle (Agudelo et al, 2014;Cervenka et al, 2017;Martin et al, 2020). However, recent evidence suggests that changes in systemic kynurenine metabolites with different perturbations may stem from tissues systems beyond muscle because Jonsson et al (2022) have recently shown that the systemic reductions in kynurenine pathway metabolites following combined ingestion of branch-chained amino acids and one-legged endurance exercise were not associated with metabolite changes in muscle. In the present study, we did not examine changes in circulating levels of kynurenine pathway metabolites; therefore, how the changes in muscle kynurenine pathway metabolites with age and exercise training contribute to circulating levels remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of kynurenine pathway metabolites can occur from several organ systems, with kynurenine mainly derived from the liver, whereas the conversion of kynurenine to kynurenic acid with exercise training is proposed to occur in muscle (Agudelo et al, 2014;Cervenka et al, 2017;Martin et al, 2020). However, recent evidence suggests that changes in systemic kynurenine metabolites with different perturbations may stem from tissues systems beyond muscle because Jonsson et al (2022) have recently shown that the systemic reductions in kynurenine pathway metabolites following combined ingestion of branch-chained amino acids and one-legged endurance exercise were not associated with metabolite changes in muscle. In the present study, we did not examine changes in circulating levels of kynurenine pathway metabolites; therefore, how the changes in muscle kynurenine pathway metabolites with age and exercise training contribute to circulating levels remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Each pool was then homogenized (Apro et al., 2015 ) and aliquoted for subsequent analysis of (1) citrate synthase activity using a spectrophotometric assay (Alp et al., 1976 ), (2) muscle glycogen content using a fluorometric assay (Harris et al., 1974 ; Lowry & Passonneau, 1972 ), (3) muscle amino acid concentrations using ultra‐performance liquid chromatography (Jonsson et al., 2022 ), and (4) total expression of selected proteins employing western blot (Apro et al., 2015 ). See specific references for more details.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Animal studies showed that supplementation of leucine induced slow-fiber-related genes and transformed skeletal muscle fiber type from fast-twitch to slow-twitch [ 46 , 47 ]. Furthermore, BCAA supplementation in healthy young adults during endurance exercise training significantly increased the expression of skeletal muscle peroxisome proliferator-activated receptor gamma coactivator-1a (PGC-1a) mRNA content after exercise, which is a marker of slow-twitch muscle fiber [ 48 ]. However, another study showed that leucine supplementation did not change the type of skeletal muscle fibers in healthy young men [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, it was reported that high circulating levels of kynurenine or a high kynurenine-to-tryptophan ratio were associated with an increased risk of depressive symptoms [ 64 , 65 ]. Jonsson et al reported that a single administration of BCAA during exercise decreased plasma levels of kynurenine but did not change plasma levels of tryptophan [ 48 ]. Although serum kynurenine levels and the kynurenine-to-tryptophan ratio in our study did not change during measurements in the fasting state, those levels might transiently decrease after ingestion of BCAA, subsequently improving the depressive state in the BCAA group.…”
Section: Discussionmentioning
confidence: 99%